Topology optimisation of masonry units from the thermal point of view using a genetic algorithm - Luísa C. Sousa (2011)
The aim of this work is to find an economic single leaf masonry wall for the building construction industry with minimised heat loss through the envelope. Lightweight aggregate concrete has the potential to offer weight reduction as well as good thermal and acoustic properties without significantly compromising the wall structural properties. The article presented here describes a search for the optimal topology of lightweight concrete masonry units according to normal thermal demands. The wall performance is measured through thermal transmittance values. The thermal behaviour of the units is calculated using three-dimensional finite element simulations. The developed topology optimisation method considers a numerical evolutionary algorithm iterating over the direct analysis performed by the finite element method. The obtained optimised topology unit will contribute towards sustainability and energy saving needs of today's building construction industry.